'Coal-to-electricity' project is ongoing in north China. (15th January 2020) - Shuxue, Xu; Yueyue, Wang; Jianhui, Niu; Guoyuan, Ma
Abstract: The status of the "Coal-to-Electricity" project implemented on a large scale in North China was introduced, including the background, history, scale, etc. The main kinds of clean energy heater equipment used in the "Coal-to-Electricity" project were introduced, especially the structural type and working principle of air source water-loop heat pump were introduced and analyzed in detail. Data analysis of actual operation performance was also given. Finally, the methods used for project implementation and the problems encountered were summarized. Highlights: The status of the 'Coal to Electricity' project implemented in North China is introduced. The structural type and working principle for air source heat pump heater were introduced and analyzed in detail. The methods used for project implementation and the problems encountered were summarized.